Third Five Year Plan Volumes I and II Government of Punjab - Planning Commission (Planning Commission)
The Punjab Third Plan consists essentially of a practical programme of work in various socio-economic fields and has been framed on the basis of the actual needs of the State. It is also realistic in the sense that it is within the capacity of the State to finance and to execute. At the same time, the Plan which in a broad sense is a continuation of the Second Plan is designed to ensure that the self-generating process in the economy will be strengthened and a base will be provided which will facilitate further growth in all the sectors.
The Planning Department Government of Punjab